Development of a Fast Valve for Disruption Mitigation and its Preliminary Application to EAST and HT-7 - 庄会东 张晓东 (Plasma science & technology, 2013)
In large tokamaks, disruption of high current plasma would damage plasma facing component surfaces （PFCs） or other inner components due to high heat load, electromagnetic force load and runaway electrons. It would also influence the subsequent plasma discharge due to production of impurities during disruptions. So the avoidance and mitigation of disruptions is essential for the next generation of tokamaks, such as ITER. Massive gas injection （MGI） is a promising method of disruption mitigation. A new fast valve has been developed successfully on EAST. The valve can be opened in 0.5 ms, and the duration of open state is largely dependent on the gas pressure and capacitor voltage. The throughput of the valve can be adjusted from 0 mbar·L to 700 mbar·L by changing the capacitor voltage and gas pressure. The response time and throughput of the fast valve can meet the requirement of disruption mitigation on EAST. In the last round campaign of EAST and HT-7 in 2010, the fast valve has operated successfully. He and Ar was used for the disruption mitigation on HT-7. By injecting the proper amount of gas, the current quench rate could be slowed down, and the impurities radiation would be greatly improved. In elongated plasmas of EAST discharges, the experimental data is opposite to that which is expected.